The complexity turn in cultures' consequences on entrepreneurship, innovation, and quality-of-life - Woodside, Arch; Bernal, P.; Coduras, A. (2017)
© Springer International Publishing AG 2017. All rights reserved. This study examines influences on quality-of-life of national cultures as complex wholes and entrepreneurship activities in Brazil, Russia, India, China, Germany, and the United States. The study tests McClelland's (1961) and more recent scholars' proposition that some cultural recipes nurture entrepreneur startups while other cultures are biased toward thwarting startups. The study applies complexity theory to construct and empirically test a general theory of cultures', entrepreneurship's, and innovation's impact on quality-of-life across nations. Because culture represents a complex whole of attitudes, beliefs, values, and behavior, the study applies a set-theoretic approach to theory construction and testing of alternative cultural recipes. Each of 28 nations is scored for the level of the national cultures for each of six focal countries. The findings include presenting the complex X (national cultural recipe) with Y (entrepreneur nurture/thwart) plots of the 28 nations for the six focal nations. The findings include recognizing national cultures (Switzerland, USA) nurturing entrepreneurial behavior versus other national cultures thwarting (Brazil and India) entrepreneurial behavior. The study concludes with a call to recognize the implicit shift in cultural implicit thinking and behavior necessary for advancing national platforms of actions to nurture entrepreneurship successfully. Entrepreneur strategy implications follow from the findings including the observation that actions nurturing firm start-ups by nations low in entrepreneurship will unlikely to be successful without reducing such nations' high levels of corruption.